Potentially inappropriate medications in hospitalised elderly patients: a cross sectional study - NC, Bhavya; SS, Torgal (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Information regarding prescribing potentially inappropriate medications (PIMs) in elderly has not been well documented. Methods: The study was a cross sectional study done by analysing the case records of elderly patients admitted to general medicine and general surgery wards. The data was collected in a proforma which included patient’s name age, sex, diagnosis, investigations, and prescription. Beer’s explicit criteria 2012 were used to identify the PIMs in prescriptions. Multivariate logistic regression analysis was done to know the potential factors associated with prescribing PIMs. Results: The results showed that 44 out of 132 patients received atleast one PIM. The average number of drugs prescribed per patient was 7.5 (range 2-15). Out of 931 drugs prescribed 63 were found to be potentially inappropriate. Polypharmacy was a major factor associated with prescribing PIMs. Conclusions: Prescribing potentially inappropriate medications is common in elderly in-patients, polypharmacy being a major factor associated with prescribing PIMs.